(untitled) (Research, Society and Development, 2021)
Introduction: Nursing in genetics and genomics combines the use of genetic technologies to assist individuals with genetic diseases, providing personalized assistance. Objective: Review in the literature the current scientific production on the role of nurses in the field of genetics and genomics. Methods: It is an integrative literature review, in the period from 2015 to 2020, in the Lilacs and PubMed databases. The following descriptors were used in the databases: "Nursing", "Genetics", "Genomics". For the crossing of the descriptors, a protocol with the following Booleans was used: Nursing AND Genetics AND Genomics. As inclusion criteria, articles based on research with primary and editorial data were selected, which addressed the theme of the present study in Portuguese and English, available in full and online. Exclusion criteria were abstracts of works, theses, dissertations, reviews that used secondary data Results: After filtering based on the inclusion criteria, sixteen articles were selected according to established criteria. After reading and analyzing the articles, two thematic categories emerged, which were: “Integration of Genetics and Genomics in Nursing” and “Education in Nursing in Genetics and Genomics”. Conclusion: It is concluded that genetics and genomics are important technologies of care in nursing, especially in the care of patients with rare syndromes, therefore, it is important to continue the training of professionals about genetic knowledge.